Investigation of structural, optical and electrical conductivity of a new organic inorganic bromide: [C12H17N2]2ZnBr4. Issue 12 (10th March 2023) - Kammoun, I.; Belhouchet, M.; Ben Ahmed, A.; Lhoste, J.; Gargouri, M.
Abstract : A new organic–inorganic hybrid, namely the [C12 H17 N2 ]2 ZnBr4 compound, has been synthesized and studied by single-crystal X-ray diffraction and optical and complex impedance spectroscopy. Abstract : A new organic–inorganic hybrid, namely the [C12 H17 N2 ]2 ZnBr4 compound, has been synthesized and studied by single-crystal X-ray diffraction and optical and complex impedance spectroscopy. It crystallized in the centrosymmetric P 21 / n space group at room temperature. The asymmetric unit is constituted by [ZnBr4 ] 2− anions, showing slightly distorted tetrahedral geometry, surrounded by four organic (C12 H17 N2 ) + cations. The crystal packing is stabilized by N–H⋯Br and C–H⋯Br hydrogen bonds arranged in a three-dimensional network. The optical absorption measurement confirms the semiconductor nature with a band gap of around 3.94 eV. Additionally, the analysis of Nyquist plots (− Z ′′ vs. Z ′) shows that the electrical properties of the material are heavily dependent on frequency and temperature, indicating a relaxation phenomenon and semiconductor-type behavior. Reduction in Z ′ was observed as a function of temperature and frequency which indicates an increase in ac conductivity and the negative temperature coefficient of resistance. The frequency dependent plots of (−Z′′) show that the electrical relaxation is non-Debye in nature. The ac conductivity spectrum obeys Jonscher's universal power law. The Correlated barrier hopping model CBH has been suggested to agree with the conduction mechanism of σ ac for the [C12 H17 N2 ]2 ZnBr4 compound.